(untitled) (Sociologisk Forskning, 2024)
Criticism has been levelled at established methods for quantitatively measuring and mapping experiences of (un)safety, where safety is often defined as the absence of crime. However, safety is far more complex, relating to individuals’ social positions, bodily expressions, experiences, and the power structures we live within. We align ourselves with this broader understanding of safety, arguing that a reductionist view of safety as simply the absence of crime is problematic in the Swedish context, where safety measurements often inform municipalities’ efforts to improve safety in public spaces. Against this backdrop, this study aims to introduce an intersectionally grounded exploratory quantitative analysis of safety and provide an empirical example of the results of such an analysis. The example is based on the Swedish National Council for Crime Prevention’s (Brå) National Safety Survey (NTU) from 2019. The study’s findings illustrate the complex interplay between power structures and experiences of (un)safety in public spaces.